Our universe the thrill of extragalactic exploration as told by leading experts - Stern, Alan 1957- (Cambridge University Press, 2001)
The Universe in which we live is unimaginably vast and ancient, with countless star-systems, galaxies and extraordinary phenomena as different and strange as blackholes, dark-matter, gamma-ray bursts and nearly-invisible galaxies. From our earliest days humankind has looked to these heavens in awe. Our Universe is a fascinating collection of articles on extra-galactic astronomy and cosmology at the dawn of the 21st century. This accessible, wonderfully illustrated book has been written by some of the world's foremost astrophysicists. Some are theorists, some computational modellers, some observers, but all provide deep insight into the most cutting-edge, difficult, and bizarre topics of astrophysics. These highly personal perspectives, however, reveal more than the wonders and achievements of modern astronomy, more than its techniques and state of knowledge. Our Universe also describes what drives these extraordinary scientists and how their careers and very lives have been shaped by a burning desire to understand our Universe
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Astronomy; Cosmology